Repair of an acquired diaphragmatic hernia with surgical mesh in a foal - Kolus, Cheryl R. (Can Vet J, 2017)
A foal born with assisted delivery developed rib fractures and a diaphragmatic hernia. The hernia was repaired using surgical mesh. The filly was healthy 42 months later. Dystocia is a risk factor for rib fractures and traumatic acquired diaphragmatic herniation. Surgical mesh repair is an option for diaphragmatic defects.